Compound A398, a novel podophyllotoxin analogue: cytotoxicity and induction of apoptosis in human leukemia cells. - Alethéia L Silveira; Glaúcia V Faheina-Martins; Raquel C Maia; Demetrius A M Araújo (PLoS ONE, 2014)
Despite advances in oncology research, cancer is one of the leading causes of death worldwide. Thus, there is a demand for the development of more selective and effective antitumor agents. This study showed that A398, a novel podophyllotoxin analogue, was cytotoxic to the HT-29, MCF-7, MOLT-4 and HL-60 tumor cell lines, being less active in human peripheral blood mononuclear cells and normal cell lines FGH and IEC-6. Tests using the HepG2 lineage indicated that its metabolites do not contribute to its cytotoxicity. In the HL-60 cells, A398 induced apoptosis in a time and concentration-dependent manner, promoting mitochondrial depolarization, inhibition of Bcl-2, phosphatidylserine exposure, activation of caspases -8, -9 and -3, and DNA fragmentation. The production of reactive oxygen species does not seem to be a crucial event for the apoptotic process. Pretreatment with specific inhibitors of kinases ERK1/2, JNK and p38 resulted in an increased percentage of death induced by A398. These results indicate that the compound induced apoptosis through activation of intrinsic and extrinsic death pathways with the mechanism involving the inhibition of the MAPKs and Bcl-2. Taken together, our findings suggest that A398 has an anticancer potential, proving itself to be a candidate for preclinical studies.